Antifungal Siderophore Conjugates for Theranostic Applications in Invasive Pulmonary Aspergillosis Using Low-Molecular TAFC Scaffolds - Pfister, Joachim; Petrik, Milos; Bendova, Katerina; Matuszczak, Barbara; Binder, Ulrike; Misslinger, Matthias; Kühbacher, Alexander; Gsaller, Fabio; Haas, Hubertus; Decristoforo, Clemens (Journal of fungi (Basel, Switzerland), 2021)
Invasive pulmonary aspergillosis (IPA) is a life-threatening form of fungal infection, primarily in immunocompromised patients and associated with significant mortality. Diagnostic procedures are often invasive and/or time consuming and existing antifungals can be constrained by dose-limiting toxicity and drug interaction. In this study, we modified triacetylfusarinine C (TAFC), the main siderophore produced by the opportunistic pathogen Aspergillus fumigatus (A. fumigatus), with antifungal molecules to perform antifungal susceptibility tests and molecular imaging. A variation of small organic molecules (eflornithine, fludioxonil, thiomersal, fluoroorotic acid (FOA), cyanine 5 (Cy5) with antifungal activity were coupled to diacetylfusarinine C (DAFC), resulting in a "Trojan horse" to deliver antifungal compounds specifically into A. fumigatus hyphae by the major facilitator transporter MirB. Radioactive labeling with gallium-68 allowed us to perform in vitro characterization (distribution coefficient, stability, uptake assay) as well as biodistribution experiments and PET/CT imaging in an IPA rat infection model. Compounds chelated with stable gallium were used for antifungal susceptibility tests. [Ga]DAFC-fludioxonil, -FOA, and -Cy5 revealed a MirB-dependent active uptake with fungal growth inhibition at 16 µg/mL after 24 h. Visualization of an A. fumigatus infection in lungs of a rat was possible with gallium-68-labeled compounds using PET/CT. Heterogeneous biodistribution patterns revealed the immense influence of the antifungal moiety conjugated to DAFC. Overall, novel antifungal siderophore conjugates with promising fungal growth inhibition and the possibility to perform PET imaging combine both therapeutic and diagnostic potential in a theranostic compound for IPA caused by A. fumigatus.
Keywords: TAFC; Aspergillus fumigatus; antifungal susceptibility testing; antifungal; PET/CT; theranostics; invasive pulmonary aspergillosis; siderophore